Application of Multigene Panel Testing in Patients With High Risk for Hereditary Colorectal Cancer: A Descriptive Report Focused on Genotype-Phenotype Correlation. Issue 6 (3rd May 2022) - Park, Ji Soo; Park, Jung Won; Shin, Saeam; Lee, Seung-Tae; Shin, Sang Joon; Min, Byung Soh; Park, Soo Jung; Park, Jae Jun; Cheon, Jae Hee; Kim, Won Ho; Kim, Tae Il
Abstract : BACKGROUND: The genetic test solely based on the clinical features of hereditary colorectal cancer has limitations in clinical practice. OBJECTIVE: This study aimed to analyze the results of comprehensive multigene panel tests based on clinical findings. DESIGN: This was a cross-sectional study based on a prospectively compiled database. SETTING: The study was conducted at a tertiary hospital. PATIENTS: A total of 381 patients with high risk for hereditary colorectal cancer syndromes were enrolled between March 2014 and December 2019. MAIN OUTCOME MEASURES: The primary outcome was to describe the mutational spectrum based on genotype-phenotype concordance and discordance. RESULTS: Germline mutations were identified in 89 patients for polyposis hereditary colorectal cancer genes (76 in APC ; 4 in PTEN ; 4 in STK11 ; 3 in BMPR1A ; 1 in POLE ; 1 in POLD1 ), 89 patients for nonpolyposis hereditary colorectal cancer genes (41 in MLH1 ; 40 in MSH2 ; 6 in MSH6 ; and 2 in PMS2 ), and 12 patients for other cancer predisposition genes (1 in ATM ; 2 in BRCA1 ; 1 in BRCA2 ; 1 in BRIP1 ; 1 in MLH3 ; 1 in NBN ; 1 in PMS1 ; 1 in PTCH1 ; 1 in TP53 ; and 2 in monoallelic MUTYH ). If we had used direct sequencing tests of 1 or 2 major genes based on phenotype, 48 (25.3%) of 190 mutations would not have been detected due to technical differences (12.1%), less frequent genotype (4.2%), unclear phenotype (3.7%), and genotype-phenotype discordance (4.7%). The genotype-phenotype discordance is probably linked to compound heterozygote, less distinctive phenotype, and insufficient information for colorectal cancer risk. LIMITATIONS: This study included a small number of patients with insufficient follow-up duration. CONCLUSIONS: A comprehensive multigene panel is expected to identify more genetic mutations than phenotype-based direct sequencing, with special utility for unclear phenotype or genotype-phenotype discordance. See Video Abstract at http://links.lww.com/DCR/B844 . APLICACIÓN DE PRUEBAS DE PANEL MULTIGÉNICO EN PACIENTES CON ALTO RIESGO DE CÁNCER COLORRECTAL HEREDITARIO: INFORME DESCRIPTIVO ENFOCADO EN LA CORRELACIÓN GENOTIPO-FENOTIPO: ANTECEDENTES: La prueba genética basada únicamente en la característica clínica del cáncer colorrectal hereditario tiene limitaciones en la práctica clínica. OBJETIVO: Este estudio tuvo como objetivo analizar el resultado de pruebas integrales de panel multigénico basadas en hallazgos clínicos. DISEÑO: Este fue un estudio transversal basado en una base de datos recopilada prospectivamente. AJUSTE: El estudio se realizó en un hospital terciario. PACIENTES: Se inscribió un total de 381 pacientes con alto riesgo de síndromes de cáncer colorrectal hereditario entre marzo del 2014 y diciembre del 2019. PRINCIPALES MEDIDAS DE RESULTADO: El resultado principal fue describir el espectro mutacional basado en la concordancia y discordancia genotipo-fenotipo. RESULTADOS: Se identificaron mutaciones de la línea germinal en 89 pacientes para genes de cáncer colorrectal hereditario con poliposis (76 en APC; 4 en PTEN; 4 en STK11; 3 en BMPR1A; 1 en POLE; 1 en POLD1), 89 pacientes para genes de CCR hereditario sin poliposis (41 en MLH1; 40 en MSH2; 6 en MSH6; y 2 ​​en PMS2) y 12 pacientes por otro gen de predisposición al cáncer (1 en ATM; 2 en BRCA1; 1 en BRCA2; 1 en BRIP1; 1 en MLH3; 1 en NBN; 1 en PMS1; 1 en PTCH1; 1 en TP53; y 2 ​​en MUTYH monoalélico). Si hubiéramos utilizado pruebas de secuenciación directa de uno o dos genes principales basados ​​en el fenotipo, 48 (25, 3%) de 190 mutaciones no se habrían detectado debido a diferencias técnicas (12, 1%), genotipo menos frecuente (4, 2%), fenotipo poco claro (3, 7%) y discordancia genotipo-fenotipo (4, 7%). La discordancia genotipo-fenotipo probablemente esté relacionada con el heterocigoto compuesto, el fenotipo menos distintivo y la información insuficiente para el riesgo de cáncer colorrectal. LIMITACIONES: Este estudio incluyó una pequeña cantidad de pacientes con una duración de seguimiento insuficiente. CONCLUSIONES: Se espera que un panel multigénico completo identifique más mutaciones genéticas que la secuenciación directa basada en el fenotipo, con especial utilidad para la discordancia de fenotipo o genotipo-fenotipo poco clara. Consulte Video Resumen en http://links.lww.com/DCR/B844 . Traducción— Dr. Francisco M. Abarca-Rendon )